NIVO-TIL: combination anti-PD-1 therapy and adoptive T-cell transfer in untreated metastatic melanoma: an exploratory open-label phase I trial - Jean-Matthieu L'Orphelin; Ugo Lancien; Jean-Michel Nguyen; Francisco J.S. Coronilla; Soraya Saiagh; Julie Cassecuel; Lise Boussemart; Anne Dompmartin; Brigitte Dréno (Acta Oncologica)
I